Oculomotor inhibition of salient distractors: Voluntary inhibition cannot override selection history - Gaspelin, Nicholas; Gaspar, John M.; Luck, Steven J. (Visual cognition, 2019)
Several studies have demonstrated that salient distractors can be proactively inhibited to prevent attentional capture. Traditional theories frame attentional guidance effects such as this in terms of explicit goals. However, several researchers have recently argued that that unconscious factors - such as the features of attended and ignored items on previous trials (called selection history) - play a stronger role in guiding attention and can overpower explicit goals. The current study assessed whether voluntary inhibition can overpower selection history. We directly compared both forms of top-down control by measuring overt eye movements, which offer an unambiguous measure of which location has won the competition for attention. We repeatedly found that selection history overpowered any effects of voluntary goals, such that observers were unable to avoid fixating a salient distractor of a known color if the target had been presented in that color on the previous trial. Moreover, a salient distractor of a particular color captured gaze even when the observer had voluntarily chosen this color to be the distractor color just moments before. Taken together, these experiments suggest that the ability to inhibit a salient color singleton is primarily a result of recent experience and not a result of explicit goals.